The Role of Cardio-Ankle Vascular Index as a Predictor of Mortality in Patients on Maintenance Hemodialysis - Murakami K (Dove Medical Press, 2021)
Kouichi Murakami,1 Emi Inayama,1 Yukiko Itoh,1 Shoji Tuchiya,1 Masashi Iwasaki,2 Nobuko Tamura,1 Toshihiko Suzuki,3 Noriko Iwai,1 Junji Utino,4 Motoyuki Masai,4 Daiji Nagayama,5,6 Kohji Shirai4,6 1Seijinaki Mihama Narita Clinic, Narita City, Chiba, 286-0041, Japan; 2Seijinkai Mihama Katori Clinic, Katori City, Chiba, 287-0041, Japan; 3Seijinkai Mihama Sakura Clinic, Sakura City, Chiba, 285-0841, Japan; 4Seijinkai Mihama Hospital, Chiba City, Chiba, 261-0013, Japan; 5Nagayama Clinic, Oyama City, Tochigi, 323-0032, Japan; 6Sakura Hospital, School of Medicine Toho University, Sakura City, Chiba, 285-8741, JapanCorrespondence: Daiji NagayamaNagayama Clinic, 2-12-22, Tenjin-Cho, Oyama City, Tochigi, 323-0032, JapanTel/Fax +81-285-22-0219Email deverlast96071@gmail.comAim: Mortality rate of maintenance hemodialysis patients is known to be high. Cardio-ankle vascular index (CAVI) is an index reflecting the proper stiffness of the arterial tree from the origin of the aorta to the ankle. We aimed to clarify the utility of CAVI as a predictor of mortality in hemodialysis patients. The roles of age and nutritional conditions on survival were also examined.Methods: We followed 242 patients undergoing hemodialysis for 6 consecutive years. Data from 209 patients (mean age was 60 ± 11 years) excluding those with ankle-brachial index < 0.90 were then analyzed. CAVI and heart to ankle pulse wave velocity (haPWV) were measured using Vasera 1500.Results: Thirty-eight hemodialysis patients who died during the 6-year period had higher age, cardiothoracic ratio (CTR), CAVI, and haPWV, and lower diastolic blood pressure, albumin, phosphate, and calcium phosphate product. The Kaplan–Meier curves for cumulative survival among the tertile groups showed that the mortality rate was higher in the highest tertile (T3) compared to T1/T2 for both CAVI and haPWV. Receiver operating characteristic (ROC) analysis revealed that CAVI had better discriminatory power for all-cause mortality compared to haPWV. In the Cox-proportional hazards analyses, 1 SD increase in both parameters contributed independently to all-cause mortality [CAVI: HR 1.595 (95% CI 1.108– 2.297), haPWV: HR 1.695 (95% CI 1.185– 2.425)], as well as age and CTR. Both parameters above the cut-offs estimated in the ROC analysis (CAVI ≥ 9.2, haPWV ≥ 8.9) also had independent contributions to mortality.Conclusion: Through the 6 consecutive years of follow-up in 209 HD patients, increased CAVI might represent a major modifiable risk factor for all-cause mortality. Further research is needed to examine whether CAVI-lowering interventions contribute to improved prognosis.Keywords: hemodialysis patient, mortality, cardio-ankle vascular index, phosphorus